Pengaruh Kompetensi Aparatur, Sistem Pengendalian Internal, Komitmen Organisasi dan Partisipasi Masyarakat terhadap Akuntabilitas Pengelolaan Dana Desa - Riski Amaliya Riski; Maryono Maryono (Universitas Sains dan Teknologi Komputer, 2022)
Law Number 6 of 2014 states that Village Funds are funds sourced from the state revenue and expenditure budget that are intended for villages and are used to finance the implementation of government activities, implementation, development, community development and also community empowerment. Fund management accountability is a form of village government accountability to the community. The purpose of this study was to examine and analyze the effect of apparatus competence, internal control system, organizational commitment and community participation on village fund management accountability in Sukolilo District, Pati Regency. This study uses primary data by giving questionnaires to respondents. The population of this study is village officials and community representatives who are involved in the allocation of village funds in Sukolio District, Pati Regency, which consists of 16 villages with a total of 80 respondents. The sampling technique in this study is saturated sampling or census sampling with the data analysis tool used is multiple linear regression analysis using the SPSS 23 program. The results showed that the competence of the apparatus, internal control system, organizational commitment and community participation affected the accountability of village fund management.